Teachers’ Practices and Challenges in Applying Interactive Teaching Methods in English Language Teaching - Astuti, Ruli (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2025)
This study aimed to investigate the implementation of Interactive English Teaching Methods in elementary schools in Sidoarjo, the types of interactive methods used by teachers, and the challenges in applying these methods. A descriptive qualitative approach was employed, involving classroom observations and interviews as the primary data collection methods, supported by secondary data from books, journals, articles, and other references. Data were analyzed using Miles and Huberman’s framework, including data reduction, data display, triangulation, and drawing conclusions. The findings revealed that teachers applied various interactive teaching methods, including role-playing, project-based learning, storytelling, games, Total Physical Response (TPR), discussions, presentations, and demonstrations. These methods aimed to enhance students’ speaking, listening, reading, and writing skills while fostering engagement, collaboration, and confidence in using English. However, teachers faced several challenges in implementing interactive methods. These included limited time allocation, students’ low confidence and lack of vocabulary, uncooperative behavior during group activities, difficulties in teaching certain materials using TPR, and student boredom. The study concludes that interactive teaching methods can create an engaging and effective learning environment for elementary English learners, but successful implementation requires careful planning, classroom management, and strategies to overcome both student- and system-related challenges.